Determinants of Sustainability Report On Mining Companies In Indonesia Sharia Stock Index (ISSI) - Ria Anisatus Sholihah; Jilma Dewi Ayu Ningtyas; Happy Sista Devy; Dwi Tia Ningrum (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2025)
Sustainability Report recent years have become crucial part of Integrated Reporting, which combines financial and non-financial parameters. In Indonesia, 144 issuers have implemented Environment-Social-Governance principles and sustainability reporting. This aims of research to determine how board size, gender representation, profitability, leverage, and institutional ownership affected sustainability report disclosure. This form of field study uses explanatory research approaches based on quantitative analysis. In data analysis, statistical computation is used to evaluate the hypothesis, which is a verification using SPSS 26. This research found that the disclosure of sustainability reports is unaffected by profitability, leverage, or the participation of female directors. However, the size of the board of directors positively affects the disclosure of sustainability reports, whereas institutional ownership negatively affects sustainability reports disclosure.Keywords: Sustainability Report, Profitability, Leverage, Good Governance